What is the mechanism of action of anti-tumour necrosis factor-alpha antibody in rheumatoid arthritis? - Feldmann, M (1996)
The rationale for anti-tumour necrosis factor-alpha (anti-TNFalpha) therapy in rheumatoid arthritis (RA) is based on experiments on cultures of human rheumatoidjoint tissue, supported by experiments in animal models, all of which demonstrated that anti-TNFalpha antibody had profound effects on the disease activity. Clinical trials have substantiated this concept, and we have used the serum samples from the clinical trials, as well as biopsies to study the changes occurring during anti-TNFalpha therapy as clues to the pathogenesis of RA. The major effects of anti-TNFalpha therapy are in downregulating cytokine activity, and in reducing leucocyte trafficking to the joints.